Assessment of Nutritional Status: A Case of Tribal Children in Assam, Northeast India - Singh, J; Mondal, N (Journal of Nepal Paediatric Society, 2013)
Introduction: Thinness is a major underlying problem among children and adolescents in the developing countries including India. The present study was carried out to determine the prevalence of nutritional status among the Sonowal Kachari children aged 6-18 years of Dibrugarh district of Assam, Northeast India. Materials and Methods: The cross-sectional data on height and weight measurements were collected among 1343 (670 boys, 673 girls) children belonging to Sonowal Kachari tribal ethnic group using multi-stage stratified sampling procedure. The Body Mass Index {BMI=weight (kg)/height2 (m2)} was calculated. The new international cut-off points of Cole et al. were used to classify the magnitude of thinness. Results: The overall mean BMI was found to be significantly higher among girls than the boys (p<0.01). The overall prevalence of thinness was observed to be 25.99% (28.08% boys, 23.92% girls) (p>0.05). The prevalence of thinness was generally higher in the early age (6-11 years), but thereafter decreased with age in both sexes. Conclusion: The results of the present study clearly indicate that the nutritional status of these children is unsatisfactory. Nutritional intervention in terms of a comprehensive supplementary balanced diet and micronutrient rich or protective foods should be introduced to ameliorate the nutritional status. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7404 J Nepal Paediatr Soc. 2013;33(1):1-7.